Room for discomfort when teaching about racism - Faye, Reidun (Frontiers in Education, 2025)
Many show emotional ambivalence, and in many cases discomfort, when dealing with sensitive topics such as racism, and research has shown that teachers tend to avoid addressing racism in schools because they lack appropriate tools. This article describes a pedagogical method – giving room for discomfort – that was conducted in seminars with six groups of pre-service teachers at a Norwegian university in 2018 and 2019. The seminars focused on racism and prejudice and used virtual reality as a didactic tool. Theoretically based in the framework of the Pedagogy of discomfort, the method emphasizes that allowing room for discomfort when teaching about racism can be a valuable pedagogical strategy. By facilitating a classroom environment where both minority and majority students have space to share their perceptions of racism, including those that are uncomfortable, one can both increase understandings of racism and equip students with tools to handle situations related to racism that may arise in their future classrooms.